Magnetosonic Harmonic Falling and Rising Frequency Emissions Potentially Generated by Nonlinear Wave‐Wave Interactions in the Van Allen Radiation Belts - Liu, Nigang; Su, Zhenpeng; Zheng, Huinan; Wang, Yuming; Wang, Shui (Geophysical research letters, 2018)
Magnetosonic waves play a potentially important role in the complex evolution of the radiation belt electrons. These waves typically appear as discrete emission lines along the proton gyrofrequency harmonics, consistent with the prediction of the local Bernstein mode instability of hot proton ring distributions. Magnetosonic waves are nearly dispersionless particularly at low harmonics and therefore have the roughly unchanged frequency time structures during the propagation. On the basis of Van Allen Probes observations, we here present the first report of magnetosonic harmonic falling and rising frequency emissions. They lasted for up to 2 hr and occurred primarily in the dayside plasmatrough following intense substorms. These harmonic emission lines were well spaced by the proton gyrofrequency but exhibited a clear falling (rising) frequency characteristic in a regime with the temporal increase (decrease) of the proton gyrofrequency harmonics. Such unexpected structures might be produced by the nonlinear interactions between the locally generated magnetosonic waves at the proton gyrofrequency harmonics and a constant frequency magnetosonic wave propagating away from the Earth. Plain Language Summary Magnetosonic waves confined near the magnetospheric equator can scatter and accelerate the energetic electrons in the Van Allen radiation belts. Their precise generation and propagation processes remain the subjects of ongoing research and controversy. Here we report two new types of magnetosonic frequency‐time structures: harmonic falling and rising frequency emissions. Available data and numerical estimations tend to support that these unusual structures were produced by the nonlinear interactions between the locally generated magnetosonic waves at the proton gyrofrequency harmonics and a constant frequency magnetosonic wave propagating away from the Earth. These unexpected frequency‐time structures reported here bring new insights on the wave generation and propagation, which will be of high interest to the radiation belt and space plasma physics communities. Key Points Magnetosonic harmonic falling/rising frequency emissions were spaced by the local proton gyrofrequency Discrete magnetosonic emission lines crossed the proton gyrofrequency harmonics over a long period (up to 2 hr) Magnetosonic harmonic falling/rising frequency emissions primarily occurred in the dayside plasmatrough following intense substorms